ASUHAN KEBIDANAN KOMPREHENSIF PADA IBU S DI PRAKTIK MANDIRI BIDAN ROSDIANA - Agus susanti; Rahmah, Siti; Malia, Anna (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2023)
Introduction: Comprehensive midwifery care is a comprehensive and continuous examination of pregnant women, childbirth, newborns, postpartum and family planning. The mortality rate for mothers and babies in Indonesia is still relatively high. Efforts to accelerate the reduction in mortality rates are carried out by ensuring that every pregnant woman gets services according to the 10 T standards. The purpose of writing this article was to provide comprehensive midwifery care for the period of pregnancy, childbirth, newborns, postpartum and family planning for Mrs. L in Independent Midwifery Practice (PMB) Rosdiana, Jeunieb District, Bireuen Regency. Method: The case study method used was a type of observational case study using qualitative data conducted at PMB Rosdiana, Jeunieb District, Bireuen Regency in February-May 2023. The subject in this case study was Mrs. S aged 29 years G2P1A0 who started from pregnancy, gave birth, newborn, postpartum and family planning. Results: The results of the care provided to Mrs. S aged 29 years G2P1A0 starting from pregnancy, childbirth, newborn, postpartum and family planning went well and the mother and baby were in normal condition. Pregnancy care was carried out in 4 visits, 3 visits for newborns, 4 visits for postnatal care and the mother chose to use 3 months of injection contraception. Conclusions and Suggestions: Comprehensive midwifery care for Mrs. S at PMB Rosdiana has been carried out in accordance with midwifery care standards. However, during delivery, there was a discrepancy that was not in accordance with the standard, namely the midwife did not use sterile gloves when assisting the delivery. As for other care, there were no complications during pregnancy, childbirth, newborns, postpartum and family planning.